Integrating New Paraprofessionals Into an Old Profession - Duff, Wendy (Archivaria, 1994)
"How can a library technician catalogue and classify material, without a graduate degree?" "No one without a university degree could ever work on a reference desk!" "I have eight years experience working in this department. I have learnt everything I know on the job. How can a two-year programme teach them what I know? Well they don’t even understand how we do things around here. Who are these technicians anyway?" These questions and similar comments reverberated through Canadian libraries when library technician programmes were first proposed. Librarians, who worried that technicians would become "cheap librarians," opposed any formal training for support staff. Library clerks, afraid that their job advancement and mobility would be hindered, complained about the hiring of technicians. The development of library technicians’ programmes and the integration of their graduates into libraries has been a long and arduous process. Furthermore, the availability of trained technicians has had an immense impact on all library workers. Technicians have enabled librarians to rethink and restructure their profession. While some librarians relish being released from routine duties, others still react in fear that their jobs are at risk. Archival technicians’ programmes are just now beginning in Canada. Will archivists react with fear or joy? RÉSUMÉ Nous connaissons les programmes de techniciens en bibliothéconomie depuis quarante ans; nous assistons présentement au développement de programmes similaires dans le domaine archivistique. Comment notre profession réagira-t-elle devant ces initiatives? Cet article passe en revue l’évolution de la formation des techniciens en bibliothéconomie; il décrit les mesures que la profession de bibliothécaire a entreprise afin de pallier à ces problèmes, et enfin recommande l’intégration des techniciens en archivistique à la profession archivistique.